2007
DOI: 10.1111/j.1365-2966.2007.12474.x
|View full text |Cite
|
Sign up to set email alerts
|

Compact stellar systems around NGC 1399

Abstract: We have obtained spectroscopic redshifts of colour‐selected point sources in four wide area VLT‐FLAMES (Very Large Telescope‐Fibre Large Array Multi Element Spectrograph) fields around the Fornax cluster giant elliptical galaxy NGC 1399, identifying as cluster members 27 previously unknown faint compact stellar systems (CSS), and improving redshift accuracy for 23 previously catalogued CSS. By amalgamating our results with CSS from previous 2dF observations and excluding CSS dynamically associated with promin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…The provided errors on R eff and n are those given by GALFIT, which should be taken with caution because close to the resolution limit these errors might be underestimated. The alternative object names from the literature are from the following sources: for UCDx Firth et al (2007), X − xxx Mieske et al (2002Mieske et al ( , 2004, Yxxx references Richtler et al (2008). Some of these objects were also presented in Richtler et al (2005) with the following names: (a) Notes.…”
Section: Surface Brightness Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The provided errors on R eff and n are those given by GALFIT, which should be taken with caution because close to the resolution limit these errors might be underestimated. The alternative object names from the literature are from the following sources: for UCDx Firth et al (2007), X − xxx Mieske et al (2002Mieske et al ( , 2004, Yxxx references Richtler et al (2008). Some of these objects were also presented in Richtler et al (2005) with the following names: (a) Notes.…”
Section: Surface Brightness Analysismentioning
confidence: 99%
“…We compiled a sample of 313 UCDs and GCs in the Fornax cluster with stellar masses above M = 10 6 M (Firth et al 2007;Mieske et al 2002Mieske et al , 2004Dirsch et al 2004;Richtler et al 2008;Schuberth et al 2010), which all are confirmed Fornax members according to their radial velocities. To determine their stellar masses consistently for the full sample, we used their V-band magnitudes and (V − I) colors and calculated their V-band massto-light ratios from the simple stellar population models (SSP) of Maraston (2005).…”
Section: Surface Brightness Analysismentioning
confidence: 99%
“…Hilker et al 1999;Drinkwater et al 2000Drinkwater et al , 2003Phillipps et al 2001;Mieske et al 2004Mieske et al , 2007Mieske et al , 2009Haşegan et al 2005;Jones et al 2006;Firth et al 2007;Gregg et al 2009;Price et al 2009;Chiboucas et al 2010;Madrid et al 2010). Recently, UCDs have also been identified in several group environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the lack of such very bright UCDs, there is now a total of eight confirmed UCDs with M V < −12 mag in Centaurus (this paper, Mieske et al 2007), comparable to the numbers in Virgo/Fornax (Jones et al 2006;Firth et al 2007). Seven of those eight sources belong to the main cluster Cen30.…”
Section: Resultsmentioning
confidence: 95%
“…A new class of compact stellar systems called "ultra-compact dwarf galaxies" (UCDs, Phillipps et al 2001) has been established (Hilker et al 1999;Drinkwater et al 2000Drinkwater et al , 2003Hasegan et al 2005;Jones et al 2006;Mieske et al 2007;Firth et al 2007;Misgeld et al 2008). UCDs are characterised by typical luminosities of −13.5 < M V < −11.0 mag, half-light radii of 10 < r h < 100 pc, and masses of 2 × 10 6 < m < 10 8 M .…”
Section: Introductionmentioning
confidence: 99%